Bridging the Gap: A Review of Traditional Seismic-Resistant Construction Techniques in Srinagar and the Need for Retrofitting Strategies - Muntazir Farooq; Preetpal Singh (PT. Radja Intercontinental Publishing, 2025)
Traditional construction techniques in Srinagar, particularly Dhajji Dewari and Taq, exhibit remarkable seismic resilience due to their modular and energy-dissipating properties. However, these structures remain vulnerable to high-intensity seismic forces due to material degradation, lack of standardized retrofitting techniques, and evolving urbanization patterns. This review consolidates existing research on the seismic performance of traditional dwellings in Srinagar, highlighting the need for innovative retrofitting strategies. A comparative analysis with modern seismic-resistant designs is conducted to emphasize the strengths and limitations of traditional methods. The study identifies the absence of standardized retrofitting frameworks as a crucial research gap, necessitating collaborative efforts among engineers, policymakers, and conservationists. By integrating traditional knowledge with modern engineering paradigms, a sustainable approach to seismic risk mitigation in heritage-rich regions is proposed.